Effect of Air Temperature, Air Humidity, and Air Pressure on Rainfall Based on Measurement Result in Kototabang - Syahrul Gunawan; - Asrizal; - Hufri; Letmi Dwiridal; Ikhsan Buyung Arifin; Fahmi Rahmatia (PILLAR OF PHYSICS, 2022)
Weather has a close relationship with community activities in Kototabang. Weather information can be used so that the risk of crop failure and disaster hazards can be minimized. Research to investigate the relationship of weather parameters was carried out using descriptive research with the multiple linear regression method. The variables in this study were divided into independent variables of air temperature, air pressure, and humidity, and the available variable was rainfall. The research method used is a multiple linear regression method with secondary data measurement of AWS and AAWS in Kototabang. The multiple linear regression method aims to predict values based on independent variables. The characteristic of this method is the presupposition variable used by more than one variable. The data processing technique applied was a multiple regression linear with three predictors (temperature, humidity, and air pressure) with the characteristics of three predictors. The purpose of the translation technique, in general, is to describe the effect of the predicted parameters on rainfall. From the output obtained, it is explained that there is a positive contribution from the predictive variable to rainfall. The correlation that occurs from the output is also very strong, reaching an output value of 99.1%. Simultaneously and partially explained that there is a large enough change in the presumed parameters (air pressure, temperature, and humidity) to rainfall. This proves that there is a very rapid change between pressure, humidity, and air temperature to rainfall in Kototabang in 2020.